Apresentação - Silva, Gisele Ruiz; Pinheiro de Queiroz Silva, Elenita; Lapa Rizza, Juliana (Diversidade e Educação, 2024)
Apresentação do Dossiê Currículo, Formação de Professores/as e Educação para a Sexualidade.